Sarawak handbook of medical emergencies - Hua-Huat, Soo; Lee-Gong, Lau; Peng-Hong, Chew; Hu, Martina (C.E. Publishing, 2011)
The best book ever created for management of medical emergencies! The new edition promises great updates, coloured pages and better quality paper. Currently in its 3rd Edition. A concise collection of guidelines and protocols in local hospitals, it is a necessity for all students in the clinical years and housemanship.